Islamic Corporate Governance dan Manajemen Laba sebagai Faktor Penentu Nilai Perusahaan pada Bank Umum Syariah Periode 2020 -2024 - Firda Sarachehan; Era Yudistira; Thoyibatun Nisa; Lella Anita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the influence of Islamic Corporate Governance and earnings management as determinants of firm value in Sharia Commercial Banks during the 2020–2024 period. The approach used in this study is quantitative, employing an explanatory research design to analyze the causal relationships among variables. The research data consists of secondary data sourced from the official annual reports of each Sharia Commercial Bank. The sample was selected using purposive sampling, resulting in 13 Sharia Commercial Banks as the units of analysis. The analytical technique applied is panel data regression using the Random Effects Model, processed using EViews 12 software. The results indicate that Islamic Corporate Governance has no significant effect on firm value, while earnings management was found to have a positive and significant effect on firm value. These findings suggest that firm value tends to be more responsive to earnings management practices than to the effectiveness of Islamic Corporate Governance implementation during the study period. Furthermore, these results also indicate that Islamic corporate governance mechanisms have not yet been fully effective in optimally improving market perceptions of corporate performance, whereas companies use earnings management practices to present a seemingly better performance, thereby enhancing market response and investor perceptions of the company’s prospects.